2014
DOI: 10.1097/inf.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

Safety of In Utero and Neonatal Antiretroviral Exposure

Abstract: Support The Pediatric HIV/AIDS Cohort Study (PHACS) was supported by the Eunice Kennedy Shriver National Institute of Child Health and Human Development with co-funding from the National Institute on Drug Abuse, the National Institute of Allergy and Infectious Diseases, the Office of AIDS Research, the National Institute of Mental Health, the National Institute of Neurological Disorders and Stroke, the National Institute on Deafness and Other Communication Disorders, the National Heart Lung and Blood Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Similar findings were found in the PHACS cohort when assessing the effects of ART exposure as well as differing ART class regimens [83]. A more recent study within PHACS also evaluated cognitive outcomes in older HEU children and did not find associations between any perinatal ART class regimens and cognitive and academic scores [84]. One study from Thailand reported small reductions in Wechsler Intelligence Scale testing comparing HEU to HUU children but acknowledged the uncertainty around the long-term clinical significance of these findings [108].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar findings were found in the PHACS cohort when assessing the effects of ART exposure as well as differing ART class regimens [83]. A more recent study within PHACS also evaluated cognitive outcomes in older HEU children and did not find associations between any perinatal ART class regimens and cognitive and academic scores [84]. One study from Thailand reported small reductions in Wechsler Intelligence Scale testing comparing HEU to HUU children but acknowledged the uncertainty around the long-term clinical significance of these findings [108].…”
Section: Discussionsupporting
confidence: 63%
“…What dictates “substantial” is debatable, but many consider outcomes involving birth weight [6675], congenital defects [76–81], early neurodevelopment [8284] and growth [70,75,8587] as significant, and none of these have demonstrated a clear association with in utero HIV/ARV exposure (Table 3). Even pre-term birth, which has been shown in several studies to be associated with ART [74,8992,95] is still an early infant outcome and would occur and be managed well before adolescence, the time of disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…6, 7, 9 -11, 17 -19 Atazanavir has been implicated in possible language domain deficits in a number of studies in North America. 7,12,31 Only a small number of women were taking atazanavir-containing regimens during pregnancy in our study; hence, we did not have sufficient power to assess for expressive language deficits among our atazanavir exposed children.…”
Section: Discussionmentioning
confidence: 99%
“…For participants between 5 and 13 years of age, assessments included the Wechsler Preschool and Primary Scale of Intelligence-III (WPPSI-III) (age 5), the Wechsler Abbreviated Scale of Intelligence (ages 7, 9, 11, and 13) for cognitive status, and the Wechsler Abbreviated Individual Achievement Test (ages 7, 9, 11, and 13) for academic performance ( 42 ). We found no association between in utero exposure to any ARV regimen or class and any cognitive or academic outcome.…”
Section: Neurocognitive and Language Functioningmentioning
confidence: 99%